Experimental characterization at nanoscale of single crystal silicon fracture toughness (Fracture and Structural Integrity, 2018)
The work reviews some preliminary recent micromechanical tests aimed at the evaluation of the fracture toughness of silicon. Pre-cracked nano specimens and alternatively notched nano specimens combined with the theory of critical distances (TCD) are compared. The results show that the fracture toughness of silicon is approximately 1 MPa·m0.5, regardless of the procedure involved (i.e., pre-cracked samples or TCD). This value agrees with macro counterpart, i.e., 0.75-1.08 MPa·m0.5, and therefore the KIC is independent of the size and crystal orientation. However, by employing the TCD, the accurate control of the final crack tip which is currently very challenging, is overcome by using notched specimens. Additionally, the results give information about the crack propagation at the nanoscale. It seems that although the specimen axis deviates from the (011), the crack propagates along the cleavage plane (011) and the process develops very fast by breaking covalent bond at the crack tip. A brief discussion on beyond the breakdown of continuum theory and challenges toward nanometer scale fracture mechanics concludes the paper.
Keywords: fracture nanomechanics; silicon; nanoscale; fracture toughness